Analyzing the emerging graphene high nano composite material for tough thermal resistance in aluminum alloy. (2021) - Sharma, Aman; Islam, Anas; Sharma, Kamal
Abstract: The key goals of the paper is to present the investigation in graphene based super strong and thermal resistant nano composite material and study their structural and mechanical properties after intensive severe plastic deformation. It is observed that the mechanical properties of graphene based super strong Nano composite materials show an intensive severe plastic deformation as accumulative roll bonding process was changed. Severe plastic deformation refined grains in the aluminum alloy and increased its mechanical properties.